Analysis of the Effect of Customer Relationship Marketing Program on Customer Retention with Customer Satisfaction As Mediating Variable in CV Vapor City Semarang - Syed Khuram Shahzad (Soegijapranata Catholic University, 2023)
This study aims to analyze the influence of customer relationship marketing program and customer retention through customer satisfaction in CV Vapor City offering marketing services and retailing. The study addressed all customers of CV Vapor City and took 150 people as the respondents. A questionnaire with close ended questioned forming in 5-poin Liket scale was distributed to the respondents using google form. Using multiple regression analysis, the results conclude that customer relationship marketing programs have positive and significant effect on customer satisfaction and customer satisfaction has positive and significant effect on customer retention. Sobel test proved that customer satisfaction mediates the influence of customer relationship marketing program on customer retention. The model was good and fit. CV Vapor City can thus continue its relationship marketing programs and increase skill and attitude of the employees in serving the customers.